Lyotropic Side-Chain Liquid Crystalline Poly(6-(4-cyanobiphenyl-4′-yloxy) hexyl acrylate) in Ternary Mixtures of N-Methyl-2-pyrrolidone and Deep Eutectic Solvent for Thermal Energy Storage - Syukrina Imtiyaz Abdul Samat; Rusli Daik; Irman Abdul Rahman; Hairul A. A. Hamid; Ernie Suzana Ali (Wiley, 2026)
Indexed by ERA